ANALISIS FILM "SIAPA DIATAS PRESIDEN": REALITAS PRAKTIK OLIGARKI DALAM SISTEM DEMOKRASI DI INDONESIA - Syafirna, Farah; Rohmah, Rizqi Auliaur; Anbiya, Bakti Fatwa (DISCOURSE: Indonesian Journal of Social Studies and Education, 2024)
The film "Who is Above the President" is a study that aims to explore the reality of oligarchic practices in the democratic system in Indonesia. The film became an object of research because it was able to visualize the dynamics of political power and interactions between political elites in the context of Indonesian democracy. By using a film analysis approach and oligarchy theory, this research highlights various narrative and visual elements in films that reveal patterns of political domination by a number of oligarchic groups. The results of the analysis show that the film shows how oligarchs manipulate the political process and control power, often by exploiting democratic institutions for personal or group interests. The implications of these findings imply the importance of increasing public awareness of the dynamics of politics and oligarchy in democratic systems, as well as the need for reforms to strengthen the principles of accountability, transparency and true political participation.